MODULE DEVELOPMENT IN MATRIX MATERIAL USING THE INDONESIAN REALISTIC MATHEMATICS EDUCATION (PMRI) APPROACH FOR CLASS X OF SMK - Aprilian Dwi Putranto; Aris Thobirin (Universitas Ahmad Dahlan, 2018)
The availability of mathematics teaching materials in some schools, for example in SMK Muhammadiyah 1 Yogyakarta is still short of available, especially the new teaching materials and the providing of convenience for students in learning. This study aims to develop and test the feasibility of the Module on matrix materials with the Indonesian Realistic Mathematics Education (PMRI) approach for Grade X Students at SMK (Vocational School). The research of module development on matrix material with Indonesian realistic mathematics education approach for grade X students at SMK follows steps Research and Development (R & D) which include: (1) potential and problem, (2) data collection, (3) product design, (4) product validation, (5) design revision, (6) product trial. Research subjects are material experts, media experts, and grade X students at SMK. The technique for analyzing data uses qualitative descriptive analysis, questionnaire. The results of this research consist of five main titles, and those are (1) understanding of matrix, (2) kinds of matrix, (3) addition and subtraction of matrix, (4) matrix multiplication, (5) Determinant, minor, cofactor, adjoin and inverse matrix. According to the research results, the material expert obtained an average score of 105.3 with perfect criteria, according to the effects of media experts, which scored 77 with complete rules. The student's response to a module is excellent, with an average score of 75 after experiment 1. At the same time, in a product test, it increases to score 76,8 of average with excellent criteria. The results indicate that the Module for the Grade X students at SMK on matrix material is feasible to use in the learning process.